The semantics of the word «тәте (táte)» and other kinship terms - Kurmanbaiuly, Шерубай; Adilov, Марлен (Turkic Studies Journal, 2022)
Changing the original meaning of a word is a characteristic phenomenon of the language. In the Kazakh language, one word can be used in several meanings. It is possible that a certain word may have a figurative meaning in dialects or in samples of oral literature. An example of this is the literary word táte, which is used in dialects in the derivative or original sense of the word. The word táte in the literary language is used when referring to older female relatives. And its opposite meaning is “áke; kóke; áke jaǵynan týys aǵa” used in relation to men has a dialectical character. However, in the language of writers, especially in the works of writers who write about their birthplace, childhood, and family, this word continues to be used in its local colloquial sense. Such use is observed in earlier works, for example, in a letter to his brother Khaliolle, Abay used the word táte in the meaning of “áke”. If we consider the earlier use of the name táte, we can see that this word is used in relation to relatives on the father’s side, not only in the southern regions, but also in some areas of the west, east, and even north. It is not without reason that the term of kinship táte is used in such a vast territory in a sense that is different from the literary language, therefore, there must be an explanation for this. From the ancient Turkic monuments, one can trace the use of the word táte in the meaning of “áke, ata”. The article examines the reasons and grounds for using the word táte in the Kazakh language when referring to a man, analyzes its scope and origin.